Analisis Manajemen Pengendalian Penyakit Demam Berdarah Dengue (DBD) di Puskesmas - Roza Asnel; Selvia Rindang Ompusunggu; Suryani; Rahmi Pramulia Fitri; Kursiah Warti Ningsih (HEALTH CARE : JURNAL KESEHATAN, 2022)
Dengue Hemorrhagic Fever (DHF) is caused by the dengue virus carried by the aedes aegepty mosquito, is a public health problem that occurs every year and has an impact on people's social and economic lives. Dengue control management plays an important role in early vigilance and prevention of complications. The prevalence of dengue fever in Kampar Regency in 2020 was 271 cases. Thepurpose of the study is toconduct a management analysis of dengue disease control at the Siak Hulu Health Center 1 Kampar Regency. This type of research is analytical qualitative. Informants numbered 5 people. The instrument consists of interview guidelines, observation sheets and related documents, the analysis is carried out by triangulation sources, methods and data. The results showed that the planning variables in dengue disease control management were well implemented as seen in the planning of activity, the human resources, facilities and infrastructure and funding that supported the implementation of DHF disease control management. Implementation variables such as fogging, PSN, counseling, Epidemiological Investigations, have been carried out according to Standard Operating Procedures. The evaluation variable indicates that the program is carried out according to the plan prepared, through good cooperation and is reported regularly to the health office.